Sosialisasi Ibadah Qurban Sebagai Upaya Peningkatan Pemahaman Masyarakat Terhadap Nilai Dan Ketentuan Syari’at - Fatkhul Ulum; Baiq Raudatussolihah; Sitti Muthmainnah; Fauziah Bachtiar; Susiawati; Fathurrahman (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to improve the understanding of the congregation of the Ilham Mosque in Tetebatu Village, Palangga District, regarding the values ​​of the qurban worship and the provisions of Islamic law in its implementation. The main problem found in the community is the still low understanding of the requirements for qurban animals, procedures for slaughtering according to Islamic law, and the proper distribution of qurban meat. The implementation method uses a participatory approach through observation, socialization, educational lectures, interactive discussions, and mentoring the practice of slaughtering qurban animals. The results of the activity show an increase in the congregation's understanding of the laws of qurban, the requirements for qurban animals, procedures for halal and hygienic slaughter, as well as the social and spiritual values ​​of qurban worship. The community also showed high enthusiasm during the activity. This activity has a positive impact in building public awareness to carry out qurban worship according to Islamic law and strengthen social solidarity among the congregation.